DIFFERENCE OF FETUIN-A LEVEL IN TYPE 2 DIABETES MELLITUS WITH CORONER HEARTH DISASE AND WITHOUT CORONER HEART DISEAS - Tetty Wahyuni Panjaitan, ZulfikarLubis & Santi Syafril (International Journal of Research Science and Management, 2020)
Background FetuinFetuin- A a glycoprotein that forms in the liver and has a strong relationship with the occurrence of type 2 DM. FA inhibits the autophosphorylation process of insulin receptors, suppresses adiponectin and inhibits vascular calcification. Increased levels of FA with decreased levels of adiponectin cause insulin resistance. Insulin resistance causes hyperglycemia. Continuous hyperglycemia will cause inflammation and impaired blood fat metabolism resulting in accumulation of fat in blood vessels known as atherosclerosis. Method A cross sectional study design was carried out at the Clinical Pathology Unit of RSUP. H. Adam Malik (HAM) Medan in January 2018. Subjects were patients with type 2 diabetes mellitus who were treated at the Cardiology Polyclinic and Endocrinology Polyclinic of the Department of Internal Medicine Haji Adam Malik General Hospital, Medan. As many as 20 people with type 2 diabetes mellitus (male12, female 8) and type 2 DM sufferers without CHD as many as 20 people (male 9, female 11). Data is processed and analyzed on a computer program. To see the difference in FA levels in type 2 DM with CHD and without CHD used t-test when paired with normal distribution, if not normally distributed, the Man Whitney test is used. The value of p <0.05 was stated as significant. Result and Discussion There was a significant difference in FA levels between groups of type 2 DM patients with CHD (207.07 ± 16.01) and type 2 DM patients without CHD (294.85 ± 10.97) with P = 0.000 (P <0.05). Conclusion and Suggestion FA can be used as an initial marker of the occurrence of vascular calcification in patients with type 2 diabetes. It is necessary to screen the FA examination in patients with type 2 diabetes mellitus in order to find out the process of vascular calcification has occurred since the beginning.